Destruction of microparticles related to dusty plasma processes and possible technological applications - Morozova, T.I.; Kopnin, S.I.; Popel, S.I. (Вопросы атомной науки и техники, 2012)
A method of destruction of microparticles related to dusty plasma processes is discussed. The method includes the achievement of anomalously high dust particle charges, for which the destruction process of the particles starts. Technological applications of dust particle destruction can be associated with the separation of nano- and microscale monomineral fractions from polymineral microparticles, that is of practical interest for enhancement of the efficiency of development of low-grade deposits and reprocessing of ore dumps and tailings which contain a definite amount of noble metals in the form of fine-dispersed fractions. Обсуждается метод дробления микрочастиц в плазменно-пылевых процессах. Метод включает достижение аномально высоких зарядов пылевых частиц, при которых начинается их разрушение. Технологическое применение разрушения частиц может быть связано с разделением полиминеральных частиц на нано- и микромасштабные мономинеральные фракции, что представляет практический интерес с точки зрения повышения эффективности разработки рудных месторождений и переработки рудных отвалов и хвостохранилищ, содержащих определенное количество благородных металлов в виде тонковкрапленных фракций. Обговорюється метод дроблення мікрочастинок в плазмово-пилових процесах. Метод включає досягнення аномально високих зарядів пилових частинок, при яких починається їх руйнування. Технологічне застосування руйнування частинок може бути пов'язано з поділом полімінеральних частинок на нано- і мікромасштабні мономінеральні фракції, що представляє практичний інтерес з точки зору підвищення ефективності розробки рудних родовищ і переробки рудних відвалів і хвостосховищ, що містять певну кількість благородних металів у вигляді тонковкраплених фракцій.